Material Challenges for Corrosive Environments and High Temperatures in Lead-Cooled Fast Reactor - Janah, Yulia Miftah Hul; Angelina, Tsania Eksa; Mustari, Asril Pramutadi Andi (Institut Teknologi Bandung, 2024)
Research on one of the generation IV reactors, the Lead-Cooled Fast Reactor (LFR), began in the 1950s. The development of this reactor continues until now. However, there are material challenges in the development of LFR. LFR coolant that uses liquid Pb or Pb-Bi is one of the challenges in this reactor because it causes severe corrosion. Researchers have tested various materials such as steel, ceramics, composites, and refractory alloys in liquid Pb or Pb-Bi environments to assess their corrosion resistance. These materials have shown improved radiation performance at high temperatures and have been developed (such as ODS, FeCrAl, SS316, AISI 316 EP823, AISI 304, and HCM12A). However, these materials are not yet sufficiently compatible with corrosion performance. The results indicate that no metal or ceramic material currently proves to be completely resistant to corrosion and radiation over the long term. The LFR system is intriguing but has limited applicability until suitable construction material designs are further identified.